Somatic SNPs of the BRCA2 gene at the fragments encoding RAD51 binding sites of canine mammary tumors - Ozmen, O.; Kul, S.; Risvanli, A.; Ozalp, G.; Sabuncu, A.; Kul, O. (Wiley, 2017)
Mammary tumors are the most common tumor type both in women and in female dogs. In women, heritable breast cancers have been linked mutations in the breast cancer susceptibility gene BRCA2 and it contains eight BRC repeats in exon 11 that bind to RAD51. In this study, we investigated the sequence variations of BRC1-BRC8 and C-terminus of canine BRCA2 gene. From a total of 64 canine patients with mammary tumors, 31 mammary tumors with benign and malign carcinomas and the 3 normal mammary glands were used for the study. In this study, 19 SNPs of exon 11 of BRCA2 in canine mammary tumors were detected for the first time. The c.2383A>C (T1425P) SNP was found to be the most probable disease-associated nsSNP. Our findings suggest that T1425P variation in BRC3 to be the most probable disease-associated nsSNP and may affect RAD51 binding strength.
Keywords: BRCA2; CMT; dog; RAD51; SNPs